(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article deals with the problems of recreational use of natural resources based on the example of two historical and cultural monuments located (Marmashen Monastery, Tirashen archaeological complex) in the territory of Shirak Marz of the Republic of Armenia. As a result of the research the best recreational loads have been counted.